2023
DOI: 10.3389/fpubh.2023.1127813
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Cooperative Extension's response to substance misuse: A scoping review

Abstract: BackgroundThe U.S. has experienced exponential growth in overdose fatalities over the past four decades and more than 22 million people are currently living with a substance use disorder (SUD). While great strides have been made in advancing the science of SUD prevention and treatment, proven programs and interventions are not commonly disseminated at scale in impacted communities. The U.S. Cooperative Extension System (Extension) has been recognized as a valued partner in addressing SUD in communities. Federa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…We echo the conclusions of Smith et al (2016) and Hagaman et al (2023) who acknowledge that to most effectively promote health within rural communities, we need to involve a range of community partners holding complementary roles, and to better coordinate federal funders’ dissemination strategies that impact the local level. Federal funding entities supporting TTA work, like SAMSHA, influence factors such as application of TTA theories, models, and frameworks (e.g., ISF), intensity and variety of TTA provided, and constructs targeted in TTA evaluation (Scott et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We echo the conclusions of Smith et al (2016) and Hagaman et al (2023) who acknowledge that to most effectively promote health within rural communities, we need to involve a range of community partners holding complementary roles, and to better coordinate federal funders’ dissemination strategies that impact the local level. Federal funding entities supporting TTA work, like SAMSHA, influence factors such as application of TTA theories, models, and frameworks (e.g., ISF), intensity and variety of TTA provided, and constructs targeted in TTA evaluation (Scott et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A recent scoping review of behavioral health programming delivered in Extension found that 29% of programs, activities, and strategies delivered were considered evidence-based and another 14% were evidence- or research-informed (Hagaman et al, 2023). The remainder were categorized as activities (16%; e.g., distribution of Naloxone kits), initiatives (5%; e.g., Recovery Friendly Workplace), trainings (31%; e.g., training to administer Naloxone), or resources (17%; e.g., fact sheets).…”
Section: Introductionmentioning
confidence: 99%
“…It aims to improve the health outcomes and livelihoods of the communities [ 7 ]. The CES houses a team of campus-based subject matter specialists and support county-level EPs whose activities are driven by the needs and priorities of the local communities, including the available resources from the sponsoring LGUs [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%